Sistemática e biogeografia da linhagem Tetramerium (Acanthaceae) na América do Sul - Côrtes, Ana Luiza Andrade (2013)
The genera Schaueria, Streblacanthus, Pachystachys and Thyrsacanthus represent 25% of the Tetramerium lineage (Acanthaceae: Justicieae), currently with about 40 species, distributed mainly in wetlands and drylands in South America. They are herbaceous or shrubs, with large or filiform bracts and diverse floral morphology, revealing adaptations to different pollinators. Systematic studies in the group are scarce, and the only phylogenetic study (Daniel et al. 2008) included only 10% of the species, not solving the generic limits within the lineage. The biogeography of Neotropical Tetramerium lineage is quite complex, structured in three biomes: the Amazon Forest, the Atlantic Forest and Seasonally Dry Forest. Still, there are no investigations on its diversification. Using phylogenetic and biogeographic methods based on plastid (trnL-F, trnT-L, trnS-G andrps16) and nuclear (ITS)data, we complemented and assessed the previous phylogenetic hypothesis, time-calibrated the phylogeny and reconstructed the ancestral area of Tetramerium lineage, focusing particularly on the South American genera. The analysis showed three well-defined clades and the need for a new circumscription for the genera:1- Schaueria, (excluding S. azaleiflora, S. hirsuta, S. humuliflora, S. malifolia and S. parviflora) including three new species and Justicia paranaensis; 2- Pachystachys, encompassing three species of Streblacanthus (except Streblacanthus monospermus) Schaueria azaleiflora and two new species; and 3- Thyrsacanthus, comprising also Carlowrightia sulcata, Justicia angustissima and Schaueria humuliflora, and another Mexican clade (Justicia zopilotensis, J. gonzalezii, Mirandea hyssopus and Yeatesia mabryi). The lineage originated in the Old World and dispersed to the Neotropics between the Miocene and Pliocene, reaching North America, Central America and Amazon. Between the late Miocene and early Pleistocene, the dry forests lineage expanded and, concomitantly, the rainforests lineageretracted, supporting the idea of a South American dry vegetation belt during this period. The vicariance between blocks of dry forests in southwestern South America and the Caatinga in northeastern Brazil, however, indicates a fragmentation of this vegetation at least in the Lower Pleistocene, well before the Last Glacial Maxima as proposed by the Pleistocene Arc hypothesis. Based on the phylogenetic results, we present a taxonomic revision of the genusSchaueria–including identification keys, descriptions, illustrations, comments, distribution maps and a study of pollen grains and seeds under scanning electron microscopy – and propose a new circumscription for the genus Pachystachys. Finally, we present a color guide ofphotos for South American species ofTetramerium lineage.